Utilization of health care services among insured and uninsured clients of Nirdhan Utthan Bank Limited: a cross sectional study on micro health insurance, Nepal. - Gautam, Preeti (2013)
ABSTRACT: Health Insurance with the Principle of risk sharing and risk transferring protects individual from unexpected and expensive health care cost. Among the types of health insurance practiced throughout the world, community based health insurance is the one that focus on voluntary pooling of resources for health at community level providing gateway to health care for poor and excluded family. Hence, the study aimed to compare level of health care service utilized among insured and uninsured ones. participants of the survey were interviewed using interviewed administered semi structured questionnaire method. The subsequent data were then entered in EPI info and analyzed using SPSS 20 and excel. There was no difference in the episode of illness and types of health institution visited for the treatment of disease among insured and uninsured. However insured were more admitted to hospital than uninsured. But the media days of hospitalization and cost spent during hospitalization were higher among uninsured. Higher proportion of money was spent in medicine in both cohorts. however, the cost spent on lab, x-ray and transportation were higher among insured than among uninsured . Insured borrowed or sold assets more than uninsured for the treatment of illness. However, Nirdhan Utthan Bank Limited was least used for borrowing money for health care. Majority of the respondents were satisfied with the benefits provided form Sanjeevani. However, decreasing premium, more discount on health services, discount on medicines and rewards to people who does not become sick for the entire year were the major changes in benefits that the clients of 'Sanjeevani' wished for. Also, they were keen to make payment for premium in 2-3 installments. Hence, the study compared the level of health care services utilized among insured and uninsured clients of Nirdhan utthan Bank Limited. However, longitudinal research is needed to identify the impact of healt insurance in the utilization level of health care services.